Vpliv protivnetnega zdravljenja z glukokortikosteroidi na število in težo okužb dihal pri otrocih z astmo - Kotnik, Primož (Medicinski razgledi, 1999)
Abstract. Asthma is a chronic inflammatory respiratory disease. Anti-inflammatory therapy with inhaled glucocorticosteroids is considered the most effective long-term therapy for moderate and severe forms of chronic asthma. Side effects constitute the only limitation of this therapy. The purpose of our study was to find out whet- her long-term administration of inhaled glucocorticosteroids for asthma has an imunosupresive side effect. We studied the frequency and severity of respiratory infections in asthmatic children treated with long-term inhaled glucocorticosteroids and in children with asthma receiving no such therapy. Our hypothesis was that long-term therapy with inhaled glucocorticosteroids for asthma has an imunosupressive side effect and that asthmatic children given long-term therapy with inhaled glucocorticosteroids suffer more frequent and more severe respiratory infections than children with asthma receiving no such medication. This one-year prospective study included 20 children with mild and moderate asthma,aged 7 years 0 months to 14 years 11 months (average 9 years, 4 months.There were 7 girls and 13 boys. The children were divided into two groups (n=10): one group receiving long-term therapy with inhaled glucocorticosteroids (fluticasone propionate) and another group given no such therapy. Because of moral, ethical and medical principles a non-random grouping of children was used in this study. (Abstract truncated at 2000 characters.)
Keywords: Asthma; astma; dihala; Drug therapy; infekcije; Respiratory tract infections; therapy; zdravljenje; Glucocorticoids, synthetic; Therapeutic use; Child; Administration, inhalation